Procalcitonin (PCT) levels in pulmonary tuberculosis patients with acid fast bacilli positive and negative smear at Haji Adam Malik General Hospital, Medan, Indonesia - Dina Fikry; Ricke Loesnihari; Parluhutan Siagian (DiscoverSys Inc., 2020)
Background: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which enters the droplet nuclei into the mouth or nasal passages to reach the pulmonary alveoli. The sputum smear examination for smear-positive and negative smear pulmonary tuberculosis is challenging due to requiring a longer time to get the results. Therefore, a specific marker is needed that is able to detect bacterial infections immediately, such as procalcitonin (PCT). This study aims to determine the levels of PCT in pulmonary tuberculosis patients with acid-fast bacilli positive and negative smear at Haji Adam Malik General Hospital, Medan, Indonesia.Method: A cross sectional was conducted among 40 pulmonary tuberculosis patients who met the inclusion and exclusion criteria at Haji Adam Malik General Hospital, Medan, Indonesia. The subjects were 20 positive smears and 20 negative smears. PCT examination with mini VIDAS BRAHMS was carried out using the Sandwich principle using the ELFA method (Enzyme-Linked Fluorescent Assay). Sputum examination was carried out by smear of Zhiel Neelsen smear, which was analyzed by the Mann-Whitney (Non-Parametric) test using SPSS version 17 for Windows. Results: Most of the respondents were males in both positive and negative smears group (65.0% and 70.0%, respectively) and not significantly different (P>0.05). The age of subjects was slightly older in positive smear (49.75 ± 17.993 years) compare with negative smear group (42.50 ± 14.816 years) but not statistically significant (P=0.172). The PCT levels in pulmonary tuberculosis patients with positive smear (0.1550; 21.65 ng/mL) differ significantly from the PCT levels in pulmonary tuberculosis patients with negative smear (0.05; 3.14 ng/mL) (p=0.0001). The cut off value using ROC found 0.06 ng/mL (AUC: 0.842) with a sensitivity of 80% and a specificity of 80%.Conclusion: There was a significant difference in the level of procalcitonin in patients with pulmonary tuberculosis who smear-positive and smear-negative.